Discontinued Anti-Hypertensive medication: a case control study on the stroke patients - Hossain, Mohammad Zaid; Azad, Khan Abul Kalam; Hasan, Pratyay; Hussain, Tahmeed; Rahman, Kazi Monisur; Saleh, Mohammed Abaye Deen; Kahher, Md Azizul; Ahasan, HAM Nazmul; Karim, Md Enamul (Journal of Dhaka Medical College, 2015)
Though it is long known that irregular intake of antihypertensive may cause harm, but still there is much lack of awareness among the patients in this matter. This case controlled study was done in Dhaka Medical College Hospital, Dhaka, to determine the relationship between discontinuation of antihypertensive drugs and the risk of stroke among hypertensive patients. Number of cases was 72. Control group was selected via random sampling of stroke free treated hypertensive group, similar in age to stroke cases. Sampling technique was random systematic sampling. The relationship was determined employing statistical methods including Chi-square (?2) test using computer programs, and significant association between discontinuation of antihypertensive and development of stroke in hypertensive adult patients was found ?2(1,N= 103) = 32.637, p<0.001. Odds ratio is 15.83. DOI: http://dx.doi.org/10.3329/jdmc.v22i2.21530 J Dhaka Medical College, Vol. 22, No.2, October, 2013, Page 173-178